Fiqh Jinayah's Approach to Children Trapped in the Octopus of Narcotics Trafficing - Andri Winjaya Laksana; Moh. Nurul Huda; Hendro Widodo; Dzaka Imtiyaz Iqbal; Doni Catur Saefudin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
The aim of this research is to analyze children in the narcotics distribution chain, as well as analyze the practice of jinayah fiqh in handling children as narcotics dealers. This research uses normative juridical research methods. This research is descriptive in nature, data collection in this research uses library research. The results of this research are that the ideal treatment according to jinayah fiqh is to give children the opportunity to repent. Ta’zīr sanctions can be imposed but the punishment must be proportional to the child's age and level of understanding. The state has a responsibility to prioritize religious rehabilitation as a form of protecting children's rights as well as an effort to break the chain of exploitation of children by narcotics networks. The academic contribution of this study lies in its proposed integrative approach model between fiqh jinayah and the principles of child protection within Indonesia's positive legal framework. This research provides both theoretical and practical foundations for policymakers, law enforcement officials, and Islamic educational institutions in designing more humane and transformative policies for handling children involved in drug-related offenses. The academic contribution of this study lies in offering an integrative model that bridges fiqh jinayah with contemporary child protection principles under Indonesia’s legal system, enriching scholarly discourse on Islamic criminal law and juvenile justice. Practically, this research provides a foundational framework for policymakers, law enforcement, and Islamic educational institutions to formulate more humane, restorative, and spiritually grounded responses to juvenile involvement in drug-related offenses